Pelatihan Keterampilan Menulis Hanzi pada Mahasiswa Program Studi Pendidikan Bahasa Mandarin UNM Melalui Pelatihan Menulis Hanzi - Mirâ€™ah Azizah (DEDIKASI, 2022)
Abstract. This training partner is a student of the Mandarin Education Study Program. This training is called Hanzi training. The purpose of this training is to improve Mandarin skills in writing Chinese characters. The approach used to implement this program consisted of two methods: presentation and exercise. As a result, based on the students' pre-test and post-test, Mandarin proficiency was achieved to increase from an average score of 61.69 (pre-test) to an average score of 82 (post-test).Â Keywords: Hanzi, Writing Skill, Foreign Language, Mandarin, Training